2013
DOI: 10.1109/tbme.2013.2251466
|View full text |Cite
|
Sign up to set email alerts
|

Scoliosis Follow-Up Using Noninvasive Trunk Surface Acquisition

Abstract: Abstract-Adolescent Idiopathic Scoliosis (AIS) is a musculoskeletal pathology. It is a complex spinal curvature in threedimensional space that also affects the appearance of the trunk. The clinical follow-up of AIS is decisive for its management. Currently, the Cobb angle, which is measured from full spine radiography, is the most common indicator of scoliosis progression. However, cumulative exposure to X-rays radiation increases the risk for certain cancers. Thus, a non-invasive method for the identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Goldberg et al 17 used the Quantec Spinal Imaging System in 59 patients to detect a 10-deg Cobb angle scoliosis progression over 1 year and obtained a specificity of 45% and a sensitivity of 100%. Adankon et al 18 investigated the difference between topographic measurements and Cobb angle over time in 30 patients with three clinical visits and curve progression of at least 5 deg was detected with a high sensitivity of 92% and specificity of 79%. De Korvin et al 19 used the BIOMOD ™ -L system with 100 patients and the threshold for a significant change was set to 2 deg for gibbosities and 10 deg for sinuosities.…”
Section: Discussionmentioning
confidence: 99%
“…Goldberg et al 17 used the Quantec Spinal Imaging System in 59 patients to detect a 10-deg Cobb angle scoliosis progression over 1 year and obtained a specificity of 45% and a sensitivity of 100%. Adankon et al 18 investigated the difference between topographic measurements and Cobb angle over time in 30 patients with three clinical visits and curve progression of at least 5 deg was detected with a high sensitivity of 92% and specificity of 79%. De Korvin et al 19 used the BIOMOD ™ -L system with 100 patients and the threshold for a significant change was set to 2 deg for gibbosities and 10 deg for sinuosities.…”
Section: Discussionmentioning
confidence: 99%
“…Patient Geometry, Pre-Rectification, and Post-Rectification Mould Scans White spherical markers were placed over anatomical landmarks deemed important by the orthotists involved in the study for the design of a scoliosis brace and based on previous surface topography studies that have used markers to evaluate AIS [29][30][31][32]. The location of the markers used in this study are shown in Figure 1.…”
Section: Scanning Of Patients and Mouldsmentioning
confidence: 99%
“…Moreover, a study conducted on 30 scoliotic patients showed that an Independent Component Analysis (ICA) parameterization of the trunk is able to capture local deformities such as asymmetries of the scapulae and shoulders [17].…”
Section: Trunk Surface Acquisitionmentioning
confidence: 99%